Sequencing and analysis of the complete mitochondrial genome of Amur minnow from China. (3rd July 2016) - Zhao, Shuai; Han, Xiaomin; Xu, Chunzhu
Abstract: The complete mitogenome sequence of Amur minnow ( Rhynchocypris lagowskii ) was determined using long PCR. The genome was 16, 594 bp in length and contained 13 protein-coding genes, two ribosomal RNA genes, 22 transfer RNA genes, and one control region. The overall base composition of the heavy strand is A (28.60%), C (26.32%), T (27.40%), and G (17.68%). The control region was 927 bp in length and the A + T content of the region was 63.32%. The extended termination-associated sequence domain, the central conserved domain, and the conserved sequence block domain are defined in the mitochondrial genome control region of Amur minnow. Mitochondrial genomes analyses based on maximum parsimony (MP), neighbor-joining (NJ), and Bayesian analyses yielded identical phylogenetic trees, indicating a close phylogenetic affinity of the 15 Cyprinidae species. It appeared that no less than two major phyletic lineages were present in Leuciscinae. The main clades within the Leuciscinae supported are: A clade is the Tribolodon . A clade ( Rhynchocypris ) with the Oreoleuciscus as the sister taxon to Tribolodon was supported by bootstrap values of 49%. The five different geographical populations of the R. lagowskii formed a paraphyletic group with the high bootstrap value (45%) in all examinations.